An electroactive metallo-polypyrene film as a molecular scaffold for multi-state volatile memory devices - Chhatwal, Megha; Kumar, Anup; Awasthi, Satish K.; Zharnikov, Michael; Gupta, Rinkoo D. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
In this report, an anodically electropolymerized smart film is utilized for memory storage up to quaternary states via adjustable electrical commands. The ruthenium-terpyridine complex based polypyrene film is adherent and robust enough to withstand a large number of read-write cycles (∼5 × 102) and harsh temperature conditions (∼200 °C) for facile chip-lithography. Importantly, this polymeric system is a promising molecular alternative for silicon-based static random access memory (SRAM) and provides data storage density even higher than that generated by flip-flop and flip-flap-flop logic circuits. The film enables a data storage density of up to ∼4 × 1015 bits/cm2, controlled precisely by applied voltage and accessed optically. In this way, it fulfills the essential criteria for successful realization of an economically viable molecular chip with enormous storage capability as compared to analogous silicon based devices.
Gesehen am 30.04.2020